Analisis Kinerja Dinas Pariwisata Dan Kebudayaan Kabupaten Solok Dalam Pengembangan Objek Wisata Alahan Panjang Resort - Hafiya Sherli Putri; Ida Nirwana; Arfimasri Arfimasri; Afniyeni Afniyeni (Jurnal Manajemen Pariwisata dan Perhotelan, 2023)
This study aims to analyze the performance of the Solok Regency Tourism and Culture Office in the Development of the Alahan Panjang Resort Tourism Object which is located in Nagari Alahan Panjang, Lembah Gumanti District, Solok Regency. The method in this research is a descriptive qualitative method using SWOT analysis through the IFAS and EFAS matrix approach. With the SWOT analysis, the situation of the Alahan Panjang Resort tourist attraction can be identified by identifying the internal factors and external factors that influence the tourist attraction. The research results based on the SWOT Analysis Diagram show that the coordinate position of the Performance Analysis of the Solok Regency Tourism and Culture Office in developing the Alahan Panjang Resort tourist attraction is in quadrant 1 with a cut point of 0.73; 0.33. This shows that the Alahan Panjang Resort tourist attraction is in a growth oriented strategy position or implementing a strategy referring to aggressive growth so as to enable the Solok Regency Tourism and Culture Office to carry out further development.